Or in any other way, a poem dedication for Hew Locke’s artwork The Jurors - Owen Sheers (www.situations.org.uk/projects/owen-sheers-or-in-any-other-way/, 2015)
On 15 June 2015, Hew Locke’s The Jurors was revealed for the first time as part of an international gathering of thousands of invited guests to mark the 800th anniversary of the sealing of the Magna Carta at Runnymede. To mark this occasion, Owen Sheers, poet, author and playwright was invited by Situations to write a dedication for the artwork, to be performed at the event.